Adsorption of phthalic acid esters (PAEs) on chemically aged biochars - Ghaffar Abdul; Abbas Ghulam (Green Processing and Synthesis, 2016)
Biochar offers not only agro-economic advantages, but it is also a low-cost alternative sorbent to remove water pollutants. With the passage of time and environmental exposure, biochar undergoes different biogeochemical transformations causing changes in their surface properties and composition. However, the changes in the adsorption behavior of aged biochars, under environmental conditions and efficacy of phthalic acid esters (PAEs) are still not clear. The biochar samples were prepared at two temperatures (300°C and 500°C) from peanut-shell biomass and their aging was simulated by chemical oxidation (with H2SO4/HNO3 mixture). The characteristics of the peanut-shell derived primary biochars and oxidized biochars were examined by CHN elemental analyzer, X-ray photoelectron spectroscopy (XPS), diffuse reflectance infrared Fourier-transformed (DRIFT) spectroscopy and the Brunauer-Emmet-Teller method. The oxidation introduced various functional groups to biochar surfaces, but inhibited adsorption due to the formation of three dimensional water clusters. The adsorption of PAEs on biochar was a cumulative influence of hydrophobic interactions and surface chemistry. Biochars obtained at 300°C and 500°C were distinct in their molecular structure and thus anticipated to pose different sorbent characteristics. The results suggested that exposure to different environments could cause imminent aging and influence the biochars regarding sorption properties.